Teachers’ Awareness and Utilization of Artificial Intelligence (AI) Tools for Curriculum Implementation in Secondary Schools in Anambra State (Journal of Guidance and Counselling Studies, 2025)
This study ascertained teachers’ awareness and utilization of Artificial Intelligence (AI) tools for curriculum implementation in secondary schools in Anambra State, Nigeria. Five research questions guided the study while five hypotheses were tested at 0.05 level of significance. Descriptive Survey research design was employed for the study. The population of the study comprised all the 6145 secondary school teachers in the 266 public secondary schools in Anambra State. The sample for the study comprised 600 secondary school teachers drawn from the population of the study using simple random sampling technique. The instrument for data collection is a questionnaire titled “Teachers Awareness and Utilization of Artificial Intelligence for Curriculum Implementation (TAUAICI)’’. The questionnaire was validated by three experts in Faculty of Education in Nnamdi Azikiwe University, Awka. The questionnaires were trial-tested using 20 secondary school teachers in public secondary schools in Asaba Delta State which was subjected to reliability testing using Cronbach Alpha statistics. This yielded reliability coefficient of 0.73. Frequencies, Percentage, Mean and Standard Deviation were used to answer research questions while t-test was used to test the hypothesis at 0.05 level of significance. The findings of the study revealed that while there is some exposure to a few globally recognized AI tools, the majority of AI resources remain unknown in secondary education in Anambra State. The study further revealed that AI tools serving as reference materials for the students and AI tools being used to enhance instructional delivery are the topmost benefits associated with the use of AI tools for curriculum implementation in secondary schools. On the other hand, epileptic power and poor education funding are the topmost challenges associated with the use of AI tools for curriculum implementation in secondary schools. The study further revealed that increasing fund allocation to secondary schools and equipping the school with artificial intelligence tools for curriculum implementation are the topmost strategies for enhancing teachers’ utilization of AI tools for curriculum implementation in secondary schools. The test of hypotheses showed no significant difference between the mean ratings of male and female teachers except in the utilization of AI tools they are aware of.  Based on the findings of the study, it was recommended among others that Anambra State should increase funding for secondary schools, specifically targeting the purchase and maintenance of AI tools and technology infrastructure. Efforts should be made to ensure consistent power supply in schools, facilitating the reliable use of AI tools for educational purposes